IDDF2019-ABS-0299 Gut microbiome diversity and specific microbial genera correlate with the severity of non-alcoholic liver disease in indonesia. (7th June 2019) - Olivia Maurine Jasirwan, Chyntia; Rinaldi Adhitya Lesmana, Cosmas; Hasan, Irsan; Simadibrata, Marcellus; Rinaldi, Ikhwan; Kurniawan, Juferdy; Sanityoso, Andri; Nababan, Saut; Gani, Rino Alvani
Abstract : Background: The prevalence of nonalcoholic fatty liver disease (NAFLD) is increasing. In Indonesia Hasan, I et al. (2002) reported the prevalence of 30.6%. This study evaluated the first time the profile of gut microbiota and correlation with severity of NAFLD in Indonesia. Methods: We included 37 subjects age 18–60 years. The characteristic data of the patients and the food recalls were recorded. Abdominal ultrasound, liver transient elastography with controlled attenuation parameter (CAP) were performed. Next generation 16S rRNA metagenomic sequencing was conducted using stool samples. The Spearman correlation test was used to examine the correlation between specific microbial taxa with the severity of NAFLD based on fibrosis and steatosis degree. Results: The subjects included 62.2% (n=23) females and 37.8% males (n=14), mean age 50 ± 7.93 years old. They were divided based on fibrosis and steatosis degree into non-significant and significant fibrosis using cut off 7 KPa, mild and moderate-severe steatosis based on cut off 270 dB/m. From all subjects, we got 73% vs 27% non-significant and significant fibrosis, 51.4% vs 48.6% mild and moderate-severe steatosis. At the phylum level, the proportion of Bacteriodetes did not change in fibrosis or steatosis group. The proportion of Proteobacteria and Firmicutes was different in fibrosis and steatosis groups. Actinobacteria unknown bifidobacteriales bifidobacteriaceae bifidobacterium Bifidobacterium adolescentis correlate positively with non significant fibrosis (r = 0.532; p=0.004). Firmicutes clostridia clostridiales lachnospiraceae unknown fusicatenibacter saccharivorans and Firmicutes clostridia clostridales ruminococcaceae unknown [clostridium] leptum correlate negatively with significant fibrosis (r = -0.695; p=0.026 vs r = -0.732; p=0.016). In the group of steatosis, we got Bacteroidetes bacteroidia bacteroidales rikenellaceae alistipes alistipes onderdonkii and Firmicutes clostridia clostridales oscillospiracea oscillospiraceao scilibacter ruminantum correlate negatively with moderate-severe steatosis (r = -0.478; p=0.045 vs r = -0.518; p=0.028); Bacteroidetes bacteroidia bacteroidales rikenellaceae alistipes alistipes putredinis correlate positively with mild steatosis (r = 0.503; p=0.028). Conclusions: The abundance of microbiota in NAFLD are not significantly different based on the group of fibrosis and steatosis, especially in phylum level. But at the lower level, some specific microbiota may correlate with the degree of fibrosis and steatosis.